Analisis SOAR: Dampak Penundaan Pilkada Tahun 2022 dan 2023 - Maulida Rita Widyana; Addien Fikriansyah (Badan Pengawas Pemilihan Umum, 2021)
Elections as a form of community participation must be carried out following the procedures set out in the law. One of them is in the Regional Head Election. The impact of the Covid-19 pandemic stated that the election could not be held considering that the virus outbreak was increasing every year. The assumption that the Regional Head Elections in 2022 and 2023 have been postponed has given special attention to all the pros and cons elements. The impact of the postponement of the 2022 and 2023 Regional Head Elections will happen to the KPU as the election organizer, and the complexity of the problems in the 2019 Election will repeat itself. The purpose of this study is to find the cause of the government abolishing the 2022 and 2023 Regional Head Elections in real terms by looking at the context that occurred in the simultaneous elections in 2019. This study uses qualitative descriptive methods and data collected using relevant journals, news, and also web. The theory used is an empirical political theory because it explains the predictions that will occur if the Regional Head Election is still held in 2024 by looking at the causes and effects. The analysis used is SOAR with research results in legitimacy and political parties. In legitimacy, there are regulations in the form of laws, while political parties are related to the strategies taken to win the Regional Head Election.